A programação com SCRATCH na produção de recursos nas disciplinas de arte e cultura e língua Tupi - Rabêlo, Hévellyn de Morais (2015)
It is a current challenge integrate computer into the educational curriculum. This work is an initiative that presents the planning, execution and evaluation of a course that integrate computational thinking by programming in discipline of Art and Culture and Tupi Language in Rio Tinto/PB. Then, it was proposed a course to indigenous schools to stimulate these disciplines, through the production of resources developed in the Scratch programming language, covering contents of indigenous culture. This course aims to develop computational thinking in students, through teaching programming concepts transmitted in a fun and interactive language. The course was taught with 16 hours and was guided by the constructivist learning theory. In the end, the resources developed were evaluated by a model to measure the application of computational thinking as well as their perception of computing issues. As a result, it was noticed that students mostly have achieved the best levels of development according the assessment model, thereby achieving good results.